EPEN-17. FAVORABLE OUTCOME TO INTENSIVE CHEMOTHERAPY WITHOUT IRRADIATION IN INFANTILE METASTATIC EPENDYMOMA WITH A NOVEL MOLECULAR PROFILE: A CASE REPORT. (4th December 2020) - de Faria, Flavia W; Schieffer, Kathleen M; Pierson, Christopher; Boué, Daniel; Zumberge, Nicholas; Rusin, Jerome; LaHaye, Stephanie; Miller, Katherine E; Koboldt, Daniel C; Lichtenberg, Tara; Leraas, Kristen; Brennan, Patrick; et al.
Abstract: Metastatic disease at initial presentation of intracranial ependymoma is an uncommon occurrence with only rare reports of survival and is reportedly more prevalent in the youngest of children. Clinical and molecular characteristics associated with metastatic presentation, their prognostic implications, as well as optimal treatment options for such patients, have not been identified. CASE REPORT: A seven months old child presented with posterior fossa anaplastic ependymoma; following sub-total resection of primary tumor, a spine MRI revealed leptomeningeal dissemination along the cervical spinal cord and nerve roots of the cauda equina. The patient was successfully treated with five cycles of intensive induction chemotherapy (as per Head Start with high-dose methotrexate) followed by three sequential cycles of marrow-ablative chemotherapy and autologous hematopoietic progenitor cell rescue (AuHPCR) without irradiation; he is currently without evidence of the disease now 60 months following initial diagnosis. MOLECULAR/GENOMIC RESULTS: The patient was enrolled on a patient-centric comprehensive molecular profiling protocol, which included paired tumor-normal whole-exome sequencing, RNA sequencing of the disease-involved tissue, and DNA methylation classification. The genomic profile of the tumor was relatively unremarkable, revealing only a terminal gain of chromosome 3p and a terminal deletion of chromosome 22q, suggestive of an unbalanced translocation. Using RNA sequencing, we identified a novel SPECC1L-RAF1 gene fusion. The tumor harbors unique transcriptomic and DNA methylation profiles, failing to discretely classify with well-established ependymoma subgroups. CONCLUSION: Use of genomic profiling techniques provides meaningful information for disease characterization allowing for further expansion of the molecular spectrum associated with malignant disease.